The Influence Of Internal And External Forces In Adoption Of e-CRM In Melaka And Johor SMEs - Md Nasaruddin, Nurul Hafizah (2019)
Information Technology (IT) plays a significant role in today’s business competition. A prominent role that is, it helps firms to manage relationships with customers effectively. Today’s online consumers have more complex needs and much higher expectations than ever before. Online business communities are fast emerging as new organizational tools for customer relationship management, marketing, and brand management, also for a multitude of other purposes such as building strong online trust and reciprocity. To support this capability, Customer Relationship Management (CRM) is evolving into Electronic Customer Relationship Management (e-CRM) and has become the latest paradigm in the world of Customer Relationship Management. In Malaysia, the used of eCRM in business are still scarce even though government has concerted the effort to promote technology adoption among Malaysian Small and Medium Enterprises (SMEs). The lack of understanding of what factors and how many factors influenced the adoption of e-CRM by Melaka and Johor SMEs makes it difficult for government to enourage Malaysian SMEs to use e-CRM applications and to participate in the e-marketplace. Thus, the question that have been proposed are to determine the internal and external forces associated with the adoption of e-CRM, to what extent do the factors influence the adoption and how can e-CRM practices enhanced the perfomance of SMEs. A survey was conducted using a self-administered questionnaire and the data were collected from SMEs in Melaka and Johor. The findings revealed that managers’ attitude and innovativeness played a vital role in understanding the adoption of e-CRM applications in Malaysian SMEs. In conclusion, the results showed that seven of the factors influence the adoption of e-CRM applications while one factor found not influence the adoption. Besides that, customers and suppliers are in need of information by easy internet access through various devices and platforms such as mobile devices, laptops and desktop personal computers.Thus, the uses of e-CRM improved and increased communication between organization and customers, making it an important tool for all SMEs. For the future recommendation, government need to encouraged SMEs to implement e-CRM in their business to be able to penetrate in the international market periodically and consistently.